The initial conditions for young massive cluster formation in the Galactic Centre: convergence of large-scale gas flows. Issue 1 (18th May 2022) - Williams, Bethan A; Walker, Daniel L; Longmore, Steven N; Barnes, A T; Battersby, Cara; Garay, Guido; Ginsburg, Adam; Gomez, Laura; Henshaw, Jonathan D; Ho, Luis C; Kruijssen, J M Diederik; Lu, Xing; et al.
ABSTRACT: Young massive clusters (YMCs) are compact (≲1 pc), high-mass (>10 4 M⊙ ) stellar systems of significant scientific interest. Due to their rarity and rapid formation, we have very few examples of YMC progenitor gas clouds before star formation has begun. As a result, the initial conditions required for YMC formation are uncertain. We present high resolution (0.13 arcsec, ∼1000 au) ALMA observations and Mopra single-dish data, showing that Galactic Centre dust ridge 'Cloud d' (G0.412 + 0.052, mass = 7.6 × 10 4 M⊙, radius = 3.2 pc) has the potential to become an Arches-like YMC (10 4 M⊙, r ∼ 1 pc), but is not yet forming stars. This would mean it is the youngest known pre-star-forming massive cluster and therefore could be an ideal laboratory for studying the initial conditions of YMC formation. We find 96 sources in the dust continuum, with masses ≲3 M⊙ and radii of ∼10 3 au. The source masses and separations are more consistent with thermal rather than turbulent fragmentation. It is not possible to unambiguously determine the dynamical state of most of the sources, as the uncertainty on virial parameter estimates is large. We find evidence for large-scale (∼1 pc) converging gas flows, which could cause the cloud to grow rapidly, gaining 10 4 M⊙ within 10 5 yr. The highest density gas is found at the convergent point of the large-scale flows. We expect this cloud to form many high-mass stars, but find no high-mass starless cores. If the sources represent the initial conditions for star formation, the resulting initial mass function will be bottom heavy.